Marriage from the perspectives of husband and wives What makes it last? What makes it fail? A study among selected couples in Dolores E. Samar. - Alfon, Jermaine L., et al; Bagas, Iris S. (Jermaine Alfon, 2011)
The study explored the perceptions of marriage from the perspectives of husbands and wives and the reasons why it lasts and why it fails. Fifteen couples whose years in marriage range from 20 onwards were the respondents of the study, identified purposively. The results were gathered through an in-depth interview of the 30 respondents to determine their definition of marriage, the reasons why marriage lasts and fails. Results showed that the common reason for the male respondents on why marriage lasts is understanding, love, children and faith in God. Meanwhile, love, respect, understanding, sense of being responsible, and children for the female respondents. The results showed that reasons why marriage fails includes misunderstandings, vices, lack of love and dishonesty for the male respondents. And for the female's point of view includes misunderstandings, lack of love, vices and problems within the family.